EFFECT OF POTASSIUM ON CHEMICAL AND SENSORY ATTRIBUTES OF TOMATO FRUIT - S. Javaria; M. Q. Khan; I. Bakhsh (Journal of Animal and Plant Sciences, 2012)
Fruit quality is a crucial factor in the production of tomato and potassium is the only mineral element known as the quality nutrient because of its vital role in building up of metabolites and activation of enzymes which ultimately improve chemical and sensory attributes of tomato fruit. In the present investigation effect of different rates of potassium fertilizer on chemical and sensory attributes of tomato were studied through pot experiment conducted during crop season of 2009. The pots were treated with K2O @ 0, 75, 150, 225, 300, 375, 450 Kg K2O ha-1 along with basal doses of N and P (100 Kg N and 80 Kg P2O5 ha-1, respectively). Treatments were arranged in complete randomized design. The result showed that total solids, sugars & titratible acidity increased significantly with increasing rates of potassium but contrary to above attributes the pH decreased. Similarly, lycopene, vitamin C and total soluble solids increased significantly with increased application of K2O up to 375 kg but thereafter decreased when K2O was applied @ 450 Kg K2O ha-1. Significant relationships were apparent between fertilizer rates and surface redness, tissue redness, firmness, crispness, mealinss, sweetness, sourness and flavor. Moreover, several masking effects were observed between taste active components and chemical components of tomato fruit. A positive linear correlation of flavor with sugar, total solids, titratible acidity; surface redness with lycopene & firmness with total solids while negative correlation between flavor and pH was observed. It was concluded that increasing K concentration resulted in improved quality parameters of tomato fruit and application of K2O @ 375 Kg K2O ha-1 along with recommended doses of N and P was found to be the best dose for high quality tomato fruit.
Keywords: Potassium fertilizer; tomato quality; chemical composition; sensory attributes